TAKING INTO ACCOUNT THE GENDER ASPECT AS A MEAN OF INCREASING THE EFFECTIVENESS OF LAW ENFORCEMENT ACTIVITIES (Law and Safety, 2018)
The specific problems of gender integration into the process of reforming the police force in the present conditions have been analyzed. It has been determined that gender policy in the field of law enforcement should be aimed at ensuring balanced participation of women and men in decision-making, which will contribute to the formation of a new outlook on the role of women in the police, and thus, the promotion of gender equality. The author has revealed the main components of the formation and implementation of gender policy in Ukraine, which are the gender expertise, gender statistics, gender analysis, gender education and gender management.The necessity of creating representative staffing institutions of police force has been substantiated. The recommendations for improving the construction of law enforcement system, which should provide for optimal use of human resources for improving the efficiency of professional activities of law enforcement agencies, have been formulated.It has been determined that the importance of the formation and implementation of gender policy is primarily determined by the needs of social life, the need for the effective use of human potential of Ukraine as a European state and the development of each individual. Integration of the gender component into law enforcement activities is an important mean of strengthening the people’s confidence, increasing the country’s combat capability and strengthening the rule of law in the state.
Keywords: gender; efficiency of professional activity; gender expertise; gender statistics; gender analysis